2019
DOI: 10.18488/journal.136.2019.42.253.266
|View full text |Cite
|
Sign up to set email alerts
|

Forestry Sector and Policies on Sustainable Development in Vietnam: Analyze from the Input - Output Model

Abstract: The fact that deforestation in Vietnam is one of the top problems in Vietnam. According to FAO (2005) Vietnam has the second highest rate of deforestation in the world, only behind Nigeria (Butler, 2005). There are many causes but the main reason is due to the weak management and corruption in forest protection. Types of deforestation are becoming more sophisticated and blatant such as forest conversion, approval of investment projects to deforest. In order to prevent deforestation, the Prime Minister of Vietn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Therefore, it is crucial to strengthen forest cultivation and continue expanding afforestation and greening areas, with a particular focus on Northeast China, North China, and Northwest China. It is essential to coordinate the management and construction of the mountain-water-forest-field-lake-grass-sand ecological system [29], change the planting structure of forest products, and increase the high-value timber of long-term rotation forests [30]. Furthermore, it is important to increase support and investment in forestry ecological compensation areas, protected areas, and forest management areas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to strengthen forest cultivation and continue expanding afforestation and greening areas, with a particular focus on Northeast China, North China, and Northwest China. It is essential to coordinate the management and construction of the mountain-water-forest-field-lake-grass-sand ecological system [29], change the planting structure of forest products, and increase the high-value timber of long-term rotation forests [30]. Furthermore, it is important to increase support and investment in forestry ecological compensation areas, protected areas, and forest management areas.…”
Section: Discussionmentioning
confidence: 99%
“…This study, based on the previous studies, developed the research model as shown in Fig. 1 by adopting Servant Leadership, which is a leadership that leads the organization's potential to the fullest based on democratic principles, and POS, meaning organizational commitment to members, as independent variables, Empowerment, Use of Collective Intelligence, and Continuous Learning as characteristics of organizational culture as dependent variables, and POS as a parameter to mediate causal relationship between Servant Leadership and Characteristics of Agile Organizational Culture (Hung and Trinh, 2019); (Irshad, 2017).…”
Section: Research Modelmentioning
confidence: 99%
“…There are some applications of Leontief's environmental input-output model to study the impact of economic activities on the environment through air pollutions in Vietnam such as studies of Trinh & Phong (2013), Trinh & Hoa (2017), Hung & Trinh (2019).…”
Section: Introductionmentioning
confidence: 99%